A revision of the colombian snakes of the genera leimadophis, lygophis, liophis, rhadinaea, and pliocercus, with a note on colombian coniophanes (1944)
A recent survey of approximately 200 specimens of the Colombian snakes currently assigned to the genera Leimadophis, Lygophis, Liophis, Rhadinaea, and Urotheca, has led me to offer the following analysis of these groups in Colombia.